Exposure of Human Skin Models to KrCl Excimer Lamps: The Impact of Optical Filtering. (5th February 2021) - Buonanno, Manuela; Welch, David; Brenner, David J.
Abstract: Far‐UVC radiation is a promising technology that is potentially both effective at killing airborne microbes such as coronaviruses and influenza, and being minimally hazardous to the skin and eyes. Our previous studies on health risks from far‐UVC have employed a krypton‐chloride (KrCl) excimer lamp, emitting principally at 222 nm, supplemented with an optical filter to remove longer wavelength emissions inherent to these lamps. This study explores KrCl lamp health hazards by comparing filtered and unfiltered KrCl lamps using effective spectral irradiance calculations and experimental skin exposures. Analysis of effective irradiances showed a notable increase in allowable exposure when using a filter. Induction of DNA dimers (CPD and 6‐4PP) was measured in human skin models exposed to a range of radiant exposures up to 500 mJ cm −2 . Compared to sham‐exposed tissues, the unfiltered KrCl lamps induced a statistically significant increase in the yield of both DNA lesions at all the radiant exposures studied. Conversely, filtered KrCl lamps do not induce increased levels of dimers at the current daily TLV exposure limit for 222 nm (23 mJ cm −2 ). This work supports the use of filters for far‐UVC KrCl excimer lamps when used to limit disease transmission in occupied locations. Abstract : Far‐UVC radiation is a promising tool to reduce the transmission of airborne‐mediated diseases. This study explores the skin health hazards using KrCl excimer lamps as a far‐UVC source. The KrCl lamp was tested with and without added filtration to reduce emissions outside of the 222 nm peak. The filtered KrCl lamp did not produce DNA photodamage for radiant exposures lower than 500 mJ cm −2 . Conversely, the unfiltered KrCl lamp induced a statistically significant increase in DNA dimers at all the radiant exposures studied, including the current recommended exposure limit for 222 nm radiation of 23 mJ cm −2 .